MicroRNA-29b Overexpression Decreases Extracellular Matrix mRNA and Protein Production in Human Corneal Endothelial Cells. Issue 11 (November 2016) - Toyono, Tetsuya; Usui, Tomohiko; Villarreal, Guadalupe; Kallay, Laura; Matthaei, Mario; Vianna, Lucas M. M.; Zhu, Angela Y.; Kuroda, Masahiko; Amano, Shiro; Jun, Albert S.
Abstract : Purpose: MicroRNAs are small noncoding RNAs that regulate gene expression at the posttranscriptional level. We reported that levels of microRNA (miR)-29 family are decreased in corneas of patients with Fuchs endothelial corneal dystrophy (FECD). The miR-29 family regulates the production of extracellular matrix (ECM) proteins. Accumulation of ECM proteins in Descemet membrane is an important pathologic change in FECD. In this study, we transfected miR-29b into human corneal endothelial cells and tissues and evaluated ECM protein expression levels. Methods: An immortalized Fuchs human corneal endothelial cell line (iFECD) was established by infection of corneal endothelial cells from patients with FECD with hTERT lentivirus. MiR-29b was transfected into iFECD, and the expression levels of ECMs collagen type 1 alpha 1 (COL1A1), collagen type 4 alpha 1 (COL4A1), and laminin gamma 1 (LAMC1) were evaluated with quantitative reverse transcriptase–polymerase chain reaction (qRT-PCR) and Western blot. Expression level of LAMC1 protein in miR-29b−transfected donor corneal endothelium was also evaluated by Western blot. Results: Compared with control, miR-29b expression level after transfection of iFECD was increased to 335.6% (±91.0%), and ECM expression levels were significantly decreased. Compared with control, qRT-PCR demonstrated reduction of ECM to the following levels: COL1A1: 1.9% (±0.4%); COL4A1: 7.1% (±1.7%); and LAMC1: 21.5% (±2.7%). Western blot showed reduced protein expression: COL1A1: 4.8% (±3.2%); COL4A1: 42.5% (±25.0%); and LAMC1: 44.8% (±3.1%). In miR-29b−transfected corneal tissue, LAMC1 protein expression level was decreased to 14.4% (±20.5%). Conclusions: Overexpression of miR-29b decreased ECM protein production in human corneal endothelial cells. Thus, miR-29 replacement therapy might be a new treatment strategy for FECD aimed at reducing pathologic production of ECM proteins in Descemet membrane.